Praziquantel depletion from muscle plus skin tissue of gilthead sea bream (Sparus aurata) - KOGIANNOU, DIMITRA; RIGOS, GEORGE (Mediterranean Marine Science, 2021)
This study determined the depletion pattern of praziquantel (PZQ) from gilthead sea bream (Sparus aurata) muscle plus skin tissue. Fish averaging 100.2 ± 17.7 g and kept at 25oC received a PZQ-dosing of 150 mg/kg fish for 3 days. Muscle plus skin tissue of ten fish were sampled on days 1, 2, 3, 4, and 6 days post-treatment. Depletion of PZQ from edible gilthead sea bream tissues was rapid, as PZQ concentrations decreased to 0.04 μg/g as early as 24 h post-treatment, while it was undetectable at 72 h. This information confirms the fact that PZQ is depleted fast from farmed animals, including fish such as the gilthead sea bream, and its levels in edible tissues fell below the detection limit in approximately 75 dd.